Determinants of Chronic Energy Deficiency in Pregnant Women in Ogan Ilir District - Anggraini, Junisa; Utama, Feranita; Anggraini, Rini (Karsa Husada Health Institute Garut, 2024)
In 2023, South Sumatra Province recorded a quality score of the Food Pattern of Hope (PPH), reaching 94.2, surpassing the national average. However, cases of Chronic Energy Deficiency (CED) among pregnant women remained, with a percentage of 7.4%. CED in pregnant women can lead to the birth of babies with low birth weight (LBW), disrupt fetal growth, and increase the risk of anemia during pregnancy, which can indirectly contribute to prematurity. This study aims to identify the determinant characteristics of CED in pregnant women during the second and third trimesters in Ogan Ilir Regency, South Sumatra Province. The method used is quantitative descriptive analysis. The results of the analysis showed that CED among pregnant women in their second and third trimesters in Ogan Ilir Regency occurred in determinant groups with no risk of pregnancy spacing (10.3%), sufficient antenatal care history (10%), non-risk maternal age (10.9%), and non-working mothers (9.8%). For the parity variable, five pregnant women with CED (11.9%) were from the high-risk parity category. Regarding the high-risk determinant characteristics, CED was found in low maternal education (15.2%) and low family income (11.2%). Future research is recommended to explore the determinant characteristics of CED more complexly. Additionally, optimal antenatal care (ANC) should be conducted in quantity and quality, emphasizing the importance of enhancing maternal health knowledge. Implementing the recommendation of at least two pregnancy check-ups by a doctor should also be strengthened.